On a perfect fluid Kahler spacetime - SRIVASTAVA, VIBHA; PANDEY, P. N. (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The object of the present paper is to study a perfect fluid K¨ahler spacetime. A perfect fluid K¨ahler spacetime satisfying the Einstein field equation with a cosmological term has been studied and the existence of killingand conformal killing vectors have been discussed. Certain results related to sectional curvature for pseudo projectively flat perfect fluid K¨ahler spacetime have been obtained. Dust model for perfect fluid K¨ahler spacetime has also been studied.